The possessed and the dispossessed : spirits, identity, and power in a Madagascar migrant town - Sharp, Lesley Alexandra (Comparative studies of health systems and medical care, 1996)
"This finely drawn portrait of a complex, polycultural community demonstrates that spirit possession reflects in microcosm many of the contradictions of daily life in a plantation economy. Female spirit mediums - a group heretofore assumed to be marginal - are in fact powerful and honored healers who assist their clients, the peasants and migrant laborers of Madagascar's Sambirano Valley. Lesley Sharp's wide-ranging analysis shows how spirit possession, identity, and power are intrinsically linked." "Possession by royal ancestral or tromba spirits is central to the concept of identity in Ambanja, the urban center of the Sambirano Valley. In this town there is an intense competition between insiders and outsiders. The insiders are primarily the indigenous Bemazava-Sakalava, the tera-tany or "children of the soil"; the outsiders are vahiny or "guests," labor migrants come to seek their fortunes. Yet these categories are fluid. Active participation in tromba possession confirms tera-tany status; thus migrant women who become mediums may transform their identities, becoming insiders. This action affects their daily survival, since tera-tany status confers access to arable land and local power structures." "Tromba possession also yields deeper meanings that emerge from the local knowledge of female mediums. These varied meanings are reflected in the performative aspects of healing ceremonies and are articulated through the gestures of the human body. As Sharp shows, healers' words and deeds reveal major sources of affliction, ranging from romance to urbanization and capitalist labor relations. Furthermore, spirit mediums are actively engaged in the reconstruction of indigenous history. Finally, the most powerful mediums draw on symbolic knowledge to influence the thrust of economic development in the Sambirano Valley."